A Bibliometric Analysis of Integrated Management System Research in The Electricity Business: Trends and Future Research - Irvan Khairil Solin; Made Yudi Darmita; Sandra Hendhana; RR Nindita Sri Kusumoretno (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2023)
Numerous studies have investigated integrated management system (IMS) practices in various businesses. However, bibliometric analysis in this field is still underdeveloped, particularly in the electricity business. The purpose of this study is to identify current research trends and provide recommendations for future research through bibliometric analysis of IMS research in the electricity business. The research sample included 43 papers obtained from scientific papers published in the Scopus database. Following the research findings, this study contributes by proposing future research and research trends for IMS practices in the electricity business.